The Effect of Saturation Resistivity Value for Groundwater Investigation Interpretation - Mazlan, Muhammad Naim Firdaus; Madun, Aziman (Recent Trends in Civil Engineering and Built Environment, 2024)
Identifying the position of the aquifer is essential the groundwater exploration. The method for detecting the groundwater is utilizing of electrical properties of the subsurface. The aquifer layer is known via its electrical properties of low resistivity and chargeability, represented by saturated and highly permeable subsurface layer. Then electric charge injects into the subsurface and the results of the resistivity and chargeability will be obtained. The previous studies produced a lack of resistivity and chargeability value for the samples based on their saturation. In order to obtain a new table of resistivity values based on saturation for the sample, this study was conducted in a laboratory setting by using sand box testing for sand and clay. The testing is conducted using the 4-electrode principle for the sandbox used for the sand, silt, and clay samples. A new set of resistivity values according to saturation range from the gravel and sand will be produced by conducting a resistivity laboratory test. The significance of this study was to identify the effect of saturation on electrical resistivity for groundwater representation. As an outcome of this study, it will produce the earth material-resistivity interpretation table for groundwater representation and enhance the information about the flow of groundwater and the effect of saturation toward resistivity for groundwater aims